The challenges of consent in a decentralised metaverse: exploring ethically informed protections and standards to safeguard humans - Smith, Carl Hayden; Molka-Danielsen, Judith; Webb-Benjamin, Jean-Brunel; Rasool, Jazz (Frontiers in Virtual Reality, 2025)
Throughout the history of Web2.0 there is a large body of evidence of data being used for something other than what it was consented to be used for. What were 2D webpages are becoming 3D worlds, collectively forming a Metaverse of virtual and mixed reality domains which should help to create new interactive learning, social and economic opportunities. In this paper we reflect on how the physical world will itself become a networked interface, making reality even more machine-readable, click-able, and searchable. We begin with a review of the Metaverse and some of the consent challenges that arise and urgently need to be addressed whilst exploring its potential. There is a core need for creators of Metaverse environments to make them safe spaces for everyone to use. We explore and review the knowledge gap of consent needed to ensure a fair and just use of data within the Metaverse. We explore the challenges of consent including examples such as unauthorised surveillance and the need for ethical and moral standards in large platforms such as VRChat. This need is then further elaborated using experiences gathered during the XPRIZE Rapid Re-skilling Competition. The main contributions of this paper are the five stage Shared Consent Framework which was developed in response to understanding the limitations of existing consent frameworks and the extended definition of the Metaverse.